Complications of low birth weight babies in tertiary care Hospital - Sohail Ashraf; Saba Mushtaq; Ayla Amin; Hira Tariq; Usman Ahmed; Muhammad Jahanzaib (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: In public health, Low birth weight is a significant indicator of maternal health care, poverty, healthcare delivery services, and maternal and child nutrition. The objective of this study was to determine the frequency of complications associated with low birth weight in babies.METHODOLOGY: In the pediatric department of POF Hospital (affiliated with Wah Medical College) in Wah Cantt, a prospective observational study was carried out. Study duration was 1 year (1-1-2021 to 1-1-2022). A sample size of 195 low-birth-weight babies was calculated using the WHO calculator. Non-probability convenience sampling was used to select low-birth-weight babies. Birth weight was measured in 1st 24 hours of life. Babies were followed for 1 month to understand detailed complications. The data were analyzed using SPSS version 24. The Pearson chi-square test was used. P value <0.05 was considered a significant measure.RESULTS: 195 low birth weight babies were included in the study.  There were 142(72.8%) babies with low birth weight, 29(20%) with very low birth weight, and 14(7.2%) with extremely low birth weight.  Birth weight has a significant association with both gender (p = 0.005) and gestational age (p = 0.015). Complications due to low birth weight in newborn babies were septicemia 18(9.2%), hyaline membrane disease 38(19.5%), Necrotizing enterocolitis 29(14.9%), neonatal jaundice 21(10.8%), Feeding problems 8(4.1%), etc.CONCLUSION: Low birth weight is a common factor for neonatal mortality and morbidity. A high frequency of low-birth-weight babies was found in our study. Hyaline membrane disease was the most common complication, followed by cerotizing enterococcal infection, neonatal jaundice, and septicemia.